A Case Report and Literature Review of the Outcome of Linezolid-Induced Optic and Peripheral Neuropathy in Patients With Multidrug-Resistant Pulmonary TB - Bano, Safia; Nawaz, Ahmad; Numan, Ahsan; Hassan, Muhammad Aarish; Shafique, Muhammad Bilal Ahmad (Frontiers in Neurology, 2022)
Linezolid is a second-line medication used to treat tuberculosis that has become resistant to multiple drugs. Linezolid has been shown to be effective in treating drug-resistant TB. However, long-term therapy is hampered by the related side effects, such as ocular and peripheral neuropathy. We recently encountered a 32-year-old male undergoing linezolid therapy for 12 months for multidrug-resistant tuberculosis who presented with progressive painless visual impairment and peripheral neuropathy symptoms in lower limbs as well as ataxic gait. Nerve conduction study findings of length-dependent axonal sensory polyneuropathy with bilateral optic neuropathy evident on fundoscopy suggested a case of toxic neuropathy. Following the termination of linezolid, follow-up visits revealed an improvement in visual symptoms. While there has been no discernible improvement or deterioration of peripheral neuropathy. In a developing country like Pakistan, where the rising number of cases of multidrug-resistant tuberculosis and its management is a major problem, physicians should be made aware of linezolid induced neuropathy so that close follow-up sessions for patients on long-term linezolid therapy can be arranged to avoid serious neurological consequences.